LOHC-bound hydrogen for catalytic NOx reduction from O2-rich exhaust gas. (6th October 2021) - Schröder, D.; Preuster, P.; Eßer, E.; Wasserscheid, P.; Kureti, S.
Abstract: The present study demonstrates a novel method for the NOx reduction by H2 in lean exhaust gases using H2 released from a Liquid Organic Hydrogen Carrier (LOHC). The concept implies the simultaneous H2 production and H2 -deNOx reaction, which both take place on the same catalyst. In a first approach, the catalyst was suspended in the LOHC, while the exhaust flowed through the slurry. The experiments performed with a O2 -rich model exhaust and perhydro dibenzyltoluene as LOHC as well as Pd/C, Pt/C and Pt/Al2 O3 catalysts evidenced the feasibility of this transfer hydrogenation. As a result, the Pd/C catalyst revealed best H2 -deNOx performance providing NOx conversions up to 98% above 200 °C with almost selective N2 formation. The characterization of the catalysts by temperature-programmed desorption of CO suggested that the superiority of the Pd/C sample is associated with its pronounced number of active Pd sites. Furthermore, the investigations also showed some LOHC degradation during the exposure to the lean model exhaust yielding CO, CO2 and hydrocarbons. Graphical abstract: Image 1 Highlights: A novel concept is suggested for NOx reduction by H2 released from LOHC. The concept implies simultaneous H2 formation and H2 -deNOx on same catalyst. Catalyst is suspended in the LOHC, while the NOx containing exhaust flows through it. Pd/C catalyst is very effective for combined LOHC dehydrogenation and H2 -deNOx . Number of catalytically active sites drives deNOx activity and N2 selectivity.